Electrochemical cell design and performance evaluation of polyvinyl ferrocene/carbon nanotube electrodes for selective formate separation - POLAT, SEVGİ (My University, 2023)
Selective ion separation is a fundamental challenge with applications ranging from the manufacturing of pharmaceuticals & industrial salts to water desalination. In particular, the separation of formate, a primary product of electrochemical carbon dioxide reduction, has attracted attention not only to reduce carbon emissions and energy costs but to provide new routes to value-added chemicals. In the present study, selective formate separation from an aqueous solution is demonstrated using an electrochemical flow cell with symmetric redoxactive polyvinyl ferrocene electrodes. An electrosorption system equipped with an electrosorption cell, inline conductivity, and pH sensors was constructed to provide real-time measurements of the formate adsorption performance in continuous flow mode while varying operating conditions such as the flow rate, cell voltage, and electrolyte concentration. These parameters were optimized using a Box–Behnken experimental design to improve the formate adsorption selectivity. The flow cell results showed a selectivity higher than 6.0 toward the removal of formate in an electrolyte containing a 30-fold excess of perchlorate under optimal operation conditions (i.e., 0.5 mL/min flow rate, 1.0 V, and 15 mM electrolyte concentration). The performance of the flow cell was also tested using a solution that contained different liquid CO2 reduction products, and formate separation was achieved. The results suggest that the proper design of the electrochemical cell and efficient operation of the flow platform pave the way for scaling up the technology for selective formate separation.
Keywords: Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, CHEMICAL; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences; Electrochemical selective separation; Cell design; Electrosorption; Formate; Experimental design